4,5-Dihydro-1,2,4-triazine-6-ones Condensed with Heterocycles, Part 1: Synthesis and Spectral Properties of Chiral 4,5-dihydro-6-oxo-1,2,4-triazino[4,5-b] 1,2,3,4-teterahydro-β-carbolines† - El-Abadelah, M.M.; Saleh, S.A.; Awadallah, A.M. (Asian Journal of Chemistry, 2010)
A novel series of 4,5-dihydro-6-oxo-1,2,4-triazino[4,5-b] 1,2,3,4-tetrahydro-β-carboline (5) have been prepared via direct interaction between methyl 1,2,3,4-teterahydro-β-carboine-3-carboxylate (3) and the appropriate hydrazonoyl chloride (4) of triethylamine.